Constructed wetland, an eco-technology for wastewater treatment: A review on various aspects of microbial fuel cell integration, low temperature strategies and life cycle impact of the technology. (September 2021) - Kataki, S.; Chatterjee, S.; Vairale, M.G.; Sharma, S.; Dwivedi, S.K.; Gupta, D.K.
Abstract: Constructed wetland (CW), a robust eco-technology used for wastewater reclamation can be considered as an ideal synergism among water security, energy harvesting and environmental services. The technology as an alternative to existing energy and chemical intensive treatments has attained maturity for treating contaminants from range of waste streams, under wide range of climates and conditions. Recent trend shows additional research interventions for better expansion of the technology such as energy harvesting to make the system a net energy producer by coupling CW to microbial fuel cell (CW-MFC) and improved operation under climatically challenged condition. The assessment discusses treatment efficiency, bioelectricity production, improved electrode efficiency, performance variation w.r.t. Macrophyte, emerging pollutant removal and microbial community structure in CW-MFC, which reveal that carefully designed integrated CW-MFC with optimized system elements (electrode, spacing, separator, macrophyte, C source, rhizosphere microbes) are necessary for its more profitable futuristic application. Further, low temperature challenges of the technology and the strategies to achieve satisfactory low temperature performance were assessed. Successful implementation of the technology in cold climate calls for design of CW with incorporation of appropriate heat preservation method, active macrophyte or microbial consortia to work effectively under low temperature. Comparative evaluation of the technology with other treatment processes using Life cycle assessment (LCA) with cradle to grave approach (considering alternative substrates, energy harvesting, macrophyte use and disposal options) would further boost the technology penetration. Potential research areas that appear to be worth pursuing in future to obtain further gains in CW performance are also discussed. Highlights: An optimally designed CW represents a robust multifaceted treatment system for wastewater. Well-designed CW with heat preservation measures would help its expansion in cold. CW-MFC as an energy efficient wastewater treatment option should be exploited further. LCA application on CW including end use of by-product will make the technology more sustainable.